The endocrine background of meningioma carcinogenesis - Gałązka, Jakub Krzysztof; Homa, Piotr; Domagalski, Łukasz (Journal of Education, Health and Sport, 2022)
Meningiomas, being mostly benign tumors, are derived from the arachnoid cap cells, their etiopathogenesis is based on various factors. The etiology of sporadic meningiomas is not yet known. Many factors have been identified as possible causes of the development of intracranial meningiomas. These include head trauma, viral infections, deletion in the NF2 gene, the use of cell phones, and sex hormones. The review is based on a endocrine factors, playing a role in meningioma carcinogenesis. The carcinogenesis of meningioma appeals to be profoundly dependent from hormonal factors. Mayor ones, usually underlined in according to their prognostic significance, are female sex hormones. Due to this, meningiomas are twice as more likely to occur in female than in male patients. The other group of hormones appointed to play a role in meningioma carcinogenesis are adipokines in general – and leptin in particular. Leptin secretion correlates with BMI elevation, what may explain the confirmed linking between obesity and brain tumors. The scientific literature has documented the occurrence of meningioma in five patients with CAH, but the role of cortical axis and/or ACTH secretion impairments is still under consideration. Authors didn’t find any publication about the role of thyroid disorders in meningioma carcinogenesis. The carcinogenesis of meningioma appeals to be profoundly dependent from hormonal factors. The effects of female sex hormones and adipokines are under a significant consideration, and may be useful in severity prediction. Basic science research should be focused on ACTH secretion in meningioma and possible common genetic etiopathogenesis of meningioma and CAH.